2017
DOI: 10.1016/j.psychres.2016.11.022
|View full text |Cite
|
Sign up to set email alerts
|

‘I can’t accept that feeling’: Relationships between interoceptive awareness, mindfulness and eating disorder symptoms in females with, and at-risk of an eating disorder

Abstract: Mindfulness based therapies (MBTs) for eating disorders show potential benefit for outcomes yet evidence is scarce regarding the mechanisms by which they influence remission from symptoms. One way that mindfulness approaches create positive outcomes is through enhancement of emotion regulation skills. Maladaptive emotion regulation is a key psychological feature of all eating disorders. The aim of the current study was to identify facets of emotion regulation involved in the relationship between mindfulness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 76 publications
(151 reference statements)
3
25
0
3
Order By: Relevance
“…Specifically, we tested the following: (a) Whether individuals with eating disorders differed in facets of mindfulness from a normative undergraduate sample and (b) Whether facets of mindfulness predict eating disorder symptoms over time and vice versa in individuals with eating disorders. Based on theory and previous empirical findings (Butryn et al, 2013;Compare et al, 2012;Lattimore et al, 2017), we hypothesized that (a) individuals with eating disorders would report lower acting with awareness and non-reactivity, but higher observing, than an undergraduate comparison sample and (b) higher non-reactivity and acting with awareness would prospectively predict lower future drive for thinness, bulimic symptoms, and body dissatisfaction, but that observing would prospectively predict higher eating disorder symptoms (given that previous research suggests that observing is positively associated with eating disorder symptoms). We also did not expect that eating disorder symptoms would prospectively predict future mindfulness.…”
Section: Study Purposementioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, we tested the following: (a) Whether individuals with eating disorders differed in facets of mindfulness from a normative undergraduate sample and (b) Whether facets of mindfulness predict eating disorder symptoms over time and vice versa in individuals with eating disorders. Based on theory and previous empirical findings (Butryn et al, 2013;Compare et al, 2012;Lattimore et al, 2017), we hypothesized that (a) individuals with eating disorders would report lower acting with awareness and non-reactivity, but higher observing, than an undergraduate comparison sample and (b) higher non-reactivity and acting with awareness would prospectively predict lower future drive for thinness, bulimic symptoms, and body dissatisfaction, but that observing would prospectively predict higher eating disorder symptoms (given that previous research suggests that observing is positively associated with eating disorder symptoms). We also did not expect that eating disorder symptoms would prospectively predict future mindfulness.…”
Section: Study Purposementioning
confidence: 99%
“…Compare et al found that higher acting with awareness and non‐reactivity was associated with less binge eating episodes in individuals diagnosed with BED but not controls. In three cross‐sectional studies, Lattimore et al () found differing patterns of associations between acting with awareness and non‐reactivity on the one hand and bulimic symptoms and drive for thinness on the other hand, in an eating disorder versus a non‐clinical sample. In the clinical sample, higher acting with awareness and non‐reactivity were associated with lower drive for thinness but not bulimic symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The current study used a composite of the non-reactivity, acting with awareness, and non-judging subscales. Previous use of the composite of these three subscales [63] indicates acceptable internal consistency (α = 0.79). The response format comprises a five-point Likert scale (1 = never or very rarely true; 5 = very often or always true).…”
Section: Mindfulnessmentioning
confidence: 99%
“…Finally, it is currently unclear whether the correlation between mindfulness and ED psychopathology is similar among different sample types. For example, both, Lattimore et al () and Compare et al () found differing patterns of associations between mindfulness facets and ED symptoms in an ED sample vs. healthy controls. It is also unclear whether the correlation between mindfulness and ED psychopathology is similar among different ED diagnoses, as no study to date has examined whether the magnitude of the correlation between mindfulness and ED symptoms differs depending on ED type.…”
Section: Introductionmentioning
confidence: 99%